The Influence of Golf Caddies’ Service Justice on the Word-of-Mouth and Golf Tourists’ Behavioral Intention in China - Pu, Zhou (Advances in Social Sciences Research Journal, 2024)
Prior studies of service justice’s influence on customer’s behavioral intention and word-of-mouth have been conducted in many fields, such as business and marketing, while the influence in golf tourism marketing needs to be examined. Therefore, the purpose of this study is to analyze the structural relationship among golf caddies’ service justice, word-of-mouth of golf resorts and behavioral intention of golf tourists in China. 417 data were collected by convenient sampling method and analyzed with SPSS and Amos, using correlation analysis, structural equation model analysis and meditation test. The findings supported (a) the positive influence of golf caddies’ service justice on golf resort’s word-of-mouth and golf tourists’ behavioral intention, (b) the positive influence of word-of-moth on behavioral intention and (c) the partial mediating effect of word-of-mouth between service justice and behavioral intention. Hence, the structural relationship above was explored and empirically proved.